2017
DOI: 10.3390/met7030091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Ti6Al4V Struts Made Using Selective Laser Melting and Electron Beam Melting Subject to Part Orientation

Abstract: Abstract:The use of additive manufacturing technologies to produce lightweight or functional structures is widespread. Especially Ti 6 Al 4 V plays an important role in this development field and parts are manufactured and analyzed with the aim to characterize the mechanical properties of open-porous structures and to generate scaffolds with properties specific to their intended application. An SLM and an EBM process were used respectively to fabricate the Ti 6 Al 4 V single struts. For mechanical characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 50 publications
1
45
2
1
Order By: Relevance
“…Nevertheless, the mechanical performances of SEBM-manufactured Ti-6Al-4V and Ti-6Al-4V ELI alloy products [10,12,[14][15][16] compare well with those fabricated by means of SLM [8,[12][13][14] and those produced by means of conventional casting and wrought routes [14,17].…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Nevertheless, the mechanical performances of SEBM-manufactured Ti-6Al-4V and Ti-6Al-4V ELI alloy products [10,12,[14][15][16] compare well with those fabricated by means of SLM [8,[12][13][14] and those produced by means of conventional casting and wrought routes [14,17].…”
mentioning
confidence: 75%
“…Such a unique combination is particularly advantageous for lightweight applications or whenever high specific mechanical properties and cost advantages are favorable compared to conventional machining [4,7].SEBM has become a mature technology that can rely on an extensive amount of literature, which aids the development of new applications [6]. Powder flowability plays a crucial role in the initial raking of layers which, in turn, determines the optimal density and homogeneity of a microstructure after solidification [7].Solidified SEBM microstructures are relatively fine [8,9] and frequently free of martensite, unless special SEBM conditions or very fine powders are selected, or very thin parts are fabricated [3,10,11].The absence of martensite is one of the main causes of the observed reduced mechanical properties of SEBM products compared to their selective laser melting (SLM) counterparts [12][13][14], although additional factors, such as the initial powder (average size and size distribution), part thickness, and oxygen uptake, are also relevant.Nevertheless, the mechanical performances of SEBM-manufactured Ti-6Al-4V and Ti-6Al-4V ELI alloy products [10,12,[14][15][16] compare well with those fabricated by means of SLM [8,[12][13][14] and those produced by means of conventional casting and wrought routes [14,17].It has been shown that a large range of other outstanding properties [10,12,15,18,19] can currently be achieved in SEBM-manufactured builds as a result of a better understanding of the interrelationship between process parameters (e.g., scan speed, offset focus and beam current, beam current, layer feed, offset focus, and melting paths, etc.) and of such crucial factors as microstructure [10][11][12][14]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that the surface properties can be tailored by adjusting the scan speed of the electron beam. Other researchers observed that the orientation during the building process had an influence on surface roughness because of change in energy flow [78,79].…”
Section: Role Of Scan Speedmentioning
confidence: 99%